Challenges of Timely Kawasaki Disease Diagnosis in 2-Month-Old Child: Clinical Case - Yuliya A. Ermolaeva; Ivan R. Grishkevich; Ivan V. Doroshenko; Tatiana V. Zgerskaya; Iuliia G. Samoilova; Svetlana A. Gay; Natalia A. Shmakova (Вопросы современной педиатрии)
Background. Kawasaki disease is an acute febrile systemic vasculitis occurring primarily in children under the age of five years old. It is characterized by high risk of cardiovascular complications development, including coronary vessels aneurysm. Its timely diagnosis is difficult in the absence of major clinical signs. Clinical case description. 2-month-old child developed a disease with the signs of respiratory infection, exanthema syndrome, severe anemia, thrombocytosis; he has laboratory signs of inflammation (leukocytosis, neutrophil shift, increased erythrocyte sedimentation rate and C-reactive protein level). The detection of early antibodies to cytomegalovirus infection and tick-borne borreliosis causative agent indicated the infectious nature of the disease. Clinical diagnosis was established: “Mixed infection: Lyme borreliosis, non-erythematous form, and unspecified serous meningitis, moderate severity, non-mild course. Prior disease complication: toxic-allergic dermatitis, secondary cardiopathy (toxic-infectious origin). Comorbid conditions: acquired cytomegalovirus infection, generalized form, with involvement of respiratory tract (nasopharyngotonsillitis), skin (exanthema syndrome), and hemopoietic system (severe anemia)”. The patient was transferred from somatic to infectious department, where he was administered with several courses of antibiotic therapy (ceftriaxone, cefepime, meropenem, vancomycin), antiviral drugs (viferon suppositories, acyclovir), RBC-transfusion was performed due to severe anemia. Single administration of human immunoglobulin was performed on the 18th day of the disease. The child was discharged with clinical recovery on the 35th day from the disease onset. Coronary artery aneurysm was revealed on the 30th day after discharge, retrospective diagnosis was established: Kawasaki disease. Conclusion. Prolonged fever with nonspecific clinical manifestations of Kawasaki disease resulted in its late diagnosis. The disease was revealed only after the development of typical and at the same time severe complication — coronary artery aneurysm. Pediatricians should keep awareness on cases with long-term signs of inflammation with no established infectious disease.